Development of a method for simultaneous analysis of PCDDs, PCDFs, PCBs, PBDEs, PCNs and PAHs in Antarctic air - PIAZZA, Rossano; GAMBARO, Andrea; ARGIRIADIS, ELENA; VECCHIATO, MARCO; CESCON, Paolo; BARBANTE, Carlo; S. Zambon (Analytical and Bioanalytical Chemistry, 2013)
The development of a unique analytical method for the determination of five classes of persistent organic pollutants (POPs) in atmospheric gas and the particle phase through gas chromatography coupled to high-resolution mass spectrometry is presented. Every step of the preanalytical and analytical optimization process is described. Great effort was put into simplifying the traditional techniques, with reference to EPA and literature methods. Automated instruments were used for sample extraction and cleanup in order to enhance repeatability and reduce contamination risks. Unlike most common approaches, no separation of the analytes was performed before the GC analysis in order to avoid sample fractionation and to save time and materials. This allowed low instrumental and method detection limits (pg to sub-pg) to be achieved. Accuracy and precision were tested by fortifying the matrix and analysing standard reference materials (NIST SRM 1649b Urban Dust and 2585 Organic Contaminants in House Dust). The method was applied to five samples from Terra Nova Bay, Antarctica. Concentrations of polychlorinated dibenzop-dioxins and furans (PCDD/Fs), polychlorinated biphenyls (PCBs), polychlorinated naphthalenes (PCNs), polybrominated diphenyl ethers (PBDEs) and polycyclic aromatic hydrocarbons (PAHs) are presented. Lighter compounds dominate the distribution and are mainly present in the gaseous phase. The observed pattern may be attributable to long-range transport. Results are in general agreement with literature data, where available.